2014
DOI: 10.1002/ase.1483
|View full text |Cite
|
Sign up to set email alerts
|

Integration of gross anatomy in an organ system‐based medical curriculum: Strategies and challenges

Abstract: The University of Alabama School of Medicine (UASOM) instituted a fully integrated, organ system-based preclinical curriculum in 2007. Gross anatomy and embryology were integrated with other basic science disciplines throughout the first two years of undergraduate medical education. Here we describe the methods of instruction and integration of gross anatomy and embryology in this curriculum as well as challenges faced along the way. Gross anatomy and embryology are taught through a combination of didactic lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 48 publications
0
50
1
5
Order By: Relevance
“…In the previous survey, only 53% of the respondents indicated that their discipline was part of an integrated curriculum, compared to 94% in the current survey. This finding is supported by an increasing number of reports on the integration of gross anatomy into organ system‐based curricula (Brooks et al, ) or in conjunction with specific basic science disciplines (Klement et al, ). Further analysis indicates that the average number of classroom hours has increased slightly; whereas, time in the laboratory has decreased significantly.…”
Section: Discussionmentioning
confidence: 71%
“…In the previous survey, only 53% of the respondents indicated that their discipline was part of an integrated curriculum, compared to 94% in the current survey. This finding is supported by an increasing number of reports on the integration of gross anatomy into organ system‐based curricula (Brooks et al, ) or in conjunction with specific basic science disciplines (Klement et al, ). Further analysis indicates that the average number of classroom hours has increased slightly; whereas, time in the laboratory has decreased significantly.…”
Section: Discussionmentioning
confidence: 71%
“…However, the most recent update on basic science instruction in a sampling of US medical schools shows significant reductions in course hours for gross anatomy and microanatomy (McBride and Drake, ). These changes are likely due to the implementation of integrated curriculums that have gained momentum in US schools (Van der Veken et al, ; Brauer and Ferguson, ; Brooks et al, ; Klement et al, ). McBride and Drake's survey also reported increases in the number of courses that were now part of an integrated curriculum compared to 2014: gross anatomy (94% vs. 53%), microanatomy (98% vs. 64%), neuroscience (96% vs. 25%), and embryology (92% vs. 77%).…”
Section: Discussionmentioning
confidence: 99%
“…Learning this way emulates how a clinician must eventually think, and there is an overwhelming amount of information one needs to learn in medicine that cannot feasibly be taught in only two years (Waterston and Stewart, 2005;Brooks et al, 2015). This desire is supported by the literature, which suggests that teaching basic sciences in a manner that is more consistent with clinical practice is advantageous as an integrated approach.…”
Section: Overall Analysis: Fourth-year Medical Students Residents Amentioning
confidence: 99%